Realidad, crónica y opinión: los avatares del viaje de Anna de Austria a España (1570) a través de fuentes mixtas - Esther Borrego Gutiérrez (Mélanges de la Casa de Velázquez, 2013)
Philip II’s fourth wife, his niece Anne of Austria, embarked on a long and complicated journey from Prague to Madrid, which lasted a total of five months—from 4 May 1570, the day of her wedding by proxy, until 26 November, the date of her public entrance to the Court. En route from the hostile lands of Flanders, prior to her triumphal entry in Madrid, she passed through Santander, Burgos, Valladolid and Segovia, in each of which cities she sojourned for several days, in addition to the numerous other towns and villages which she graced along the way. This article analyses the journey, which was strictly monitored by the Prudent Monarch, along with most of the official accounts from the towns that received the young queen. But however official, each one bears the trace of her personality, and in some cases one can even guess at some resentment or veiled critical allusions to the monarch’s decisions and behaviour. The variety of the celebrations described in these accounts reflects an interesting mixture of visual spectacles (such as masques and tourneys) and a mingling of genres—comedies, entremeses and books of chivalry.